Secreted frizzled related proteins: Implications in cancers - Surana, R.; Sikka, S.; Cai, W.; Shin, E.; Warrier, S.; Tan, H.; Arfuso, Frank; Fox, Simon; Dharmarajan, Arunasalam; Kumar, A. (Elsevier BV, 2014)
The Wnt (wingless-type) signaling pathway plays an important role in embryonic development, tissue homeostasis, and tumor progression becaluse of its effect on cell proliferation, migration, and differentiation. Secreted frizzled-related proteins (SFRPs) are extracellular inhibitors of Wnt signaling that act by binding directly to Wnt ligands or to Frizzled receptors. In recent years, aberrant expression of SFRPs has been reported to be associated with numerous cancers. As gene expression of SFRP members is often lost through promoter hypermethylation, inhibition of methylation through the use of epigenetic modifying agents could renew the expression of SFRP members and further antagonize deleterious Wnt signaling. Several reports have described epigenetic silencing of these Wnt signaling antagonists in various human cancers, suggesting their possible role as tumor suppressors. SFRP family members thus come across as potential tools in combating Wnt-driven tumorigenesis. However, little is known about SFRP family members and their role in different cancers. This review comprehensively covers all the available information on the role of SFRP molecules in various human cancers.